Scientific Literacy Ability of Junior High School Students on Static Electricity and Electricity in Living Things - Moh. Shohib; Yuni Sri Rahayu; Wasis Wasis; Eko Hariyono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Junior high school students need to have good scientific literacy skills to have sufficient competence to compete in the current and future era of information and globalization. Science is basic knowledge covering products, processes, and applications. One of the science materials is static electricity and electricity in living things. This study aimed to determine the literacy profile of junior high school students on static electricity and electricity in living things. The subjects of this study were junior high school students. This research uses a descriptive research method. Data collection instruments consist of scientific literacy instruments. The results showed that junior high school students’ average scientific literacy ability on static electricity and electricity in living things, in general, was low criteria. The achievement of scientific literacy ability in the first indicator to explain scientific phenomena obtained a score of 28.76% higher when compared to the second indicator evaluating and designing scientific investigations to obtain a score of 15.73%, while the third indicator to interpret data and scientific evidence obtained the lowest average score. of 10.13%. In general, the criteria for scientific literacy in all indicators are very low.